FTA agroecological approaches are implemented by the Commission on Population and Development and the United Nations Population Fund - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA presentation on innovative agroecological approaches to the expert group informing the 54th session of the Commission on Population and Development informs CPD Resolution and report of the United Nations Population Fund.